Student’s Perspective of Teacher-Student Relation in Online Class Meeting - Ade Aini Nuran; Feriyanti Elina Gultom (BAHAS, 2021)
AbstractTeacher-student relation is the most important component of language teaching.The objective of this study is Nowadays, teaching-learning process is doing by online meeting. Teacher and student can do the activity of class from home. So, based on the background it the purpose of this study is to know how the relation between teacher and student in online class meeting by the perspective of student. The methodology that was used in this research is descriptive qualitative - quantitative methodology conducted that taken 30 college students in English and Literature Department randomly at Universitas Negeri Medan. The data were collected by using a questionnaire in Google Form that was distributed it. This research is containing by various question to know how the teacher-student relation in online class by the perspective of student. The researcher made 13 questions and each question must be answer honestly by respondents.The findings of this study showed that there were the teacher-student relation in online class meeting support well. But, from the data also shown that in some cases the teacher-students relation is not build well such as online class make the limitation in communicating so the atmosphere of teacher-student relation hardly got, the teacher unreachable through online, There is no trustworthy from teacher to students about internet connection. Based on the findings, the suggestion to this study is the teacher also should treat the student fairly and more understanding.The students also should be more active and participated in online class so that they can be noticed by the teacher. Keyword :Teacher-Students Relation, English Teaching, Perspective, Online Class